Assessment of Adverse Drug Reactions in Oral Cancer Patients Receiving Chemotherapy Treatment at Tertiary Care Centres in North-Western India - Sharma, Kopal; Jasuja, Sandeep; Jain, Monica; Singh, Yatendra (Scripta Medica, 2023)
Background/Aim: Pharmacovigilance in oncology is imperative as antineoplastic drugs are two-edged swords whose irrational use can pose a major health problem and a needless financial burden on the patient. The aim of this study was to study the comprehensive safety profile of anti-neoplastic drugs used for treating oral cancers.Methods: This hospital-based prospective observational study was conducted at two premiers (a government and a private) tertiary care centres in North-Western India among newly diagnosed cases of oral cancers of both sexes between the ages of 20-70 years and requiring chemotherapy treatment. The prescribing pattern of chemotherapy drugs, associated adverse effects and potential risk factors for the development of adverse effects was studied. An adverse drug reaction (ADR) causality was assessed by the WHO-UMC algorithm and preventability by Schumock and Thornton's criteria. Univariate and multivariate logistic regression analyses were used to identify the predictors related to chemotherapy-induced adverse effects.Results: The data concerned 188 patients, of which 64.3 % developed chemotherapy-related adverse effects. Among the prescribed anti-neoplastic drugs, a combination of 5-Fluorouracil, Cisplatin and Paclitaxel regimen was associated with the majority (91.42 %) of the adverse effects. Alopecia was the most common adverse effect noted in 26.44 % of patients, followed by nausea and anaemia in 15.7 % and 9.9 % of patients, respectively. Independent predictors of chemotherapy-related adverse effects were site (Adjusted odds ratio [AOR] = 1.95; 95 % CI 1.04 - 3.62, p = 0.03), chemotherapy and radiotherapy treatment (AOR = 5.00; 95 % CI 2.62 - 9.53, p < 0.001), combination regimen of 5-Fluorouracil, Cisplatin and Paclitaxel (AOR = 8.68; 95 % CI 2.55 - 29.48, p = 0.001), associated comorbidities (AOR = 16.68; 95 % CI 2.45 - 28.34, p < 0.001). Causality assessment revealed most adverse effects (82.64 %) to be possible.Conclusion: The adverse effect varies with the type of regimen which is prescribed for the patient. Site of cancer, concomitant radiotherapy treatment and associated comorbidities were the identifiable risk factors for developing adverse effects. Onco-pharmacovigilance studies in the future will help to provide tailored treatment to patients and improve their quality of life.
Keywords: Adverse drug reactions; causality assessment; chemotherapy; oral cancers; risk factors